Daptomycin versus Vancomycin in a Methicillin-Resistant Staphylococcus aureus Endophthalmitis Rabbit Model: Bactericidal Effect, Safety, and Ocular Pharmacokinetics - Lefèvre, Sophie (American Society for Microbiology, 2012)
Staphylococcus aureus is a frequent cause of acute endophthalmitis, and infection with this virulent bacterium is often associated with a poor visual outcome. In this study, we investigated the bactericidal efficacy and the safety of intravitreal daptomycin (DAP), a lipopeptide antibiotic with broad-spectrum activity against Gram-positive bacteria, compared with those of intravitreal vancomycin (VAN) in a methicillin-resistant S. aureus endophthalmitis rabbit model. The pharmacokinetics and pharmacodynamics of daptomycin in the infected eyes were also studied. Rabbits were randomly divided into three treatment groups (n = 8) and one untreated group (n = 4), to compare the effect of single intravitreal injections of 0.2 mg and 1 mg of daptomycin (DAP 0.2 and DAP 1 groups, respectively) with that of 1 mg of intravitreal vancomycin (VAN 1 group). Vitreal aspirates were regularly collected and grading of ocular inflammation was regularly performed until euthanasia on day 7. In the DAP 0.2 group, 62.5% of the eyes were sterilized and the mean bacterial count presented a reduction of 1 log unit. In the DAP 1 and VAN 1 groups, the infection was eradicated (100% and 87.5% of eyes sterilized, respectively), with a 4-log-unit reduction of the mean bacterial count. The bactericidal efficacy in the DAP 1 group was not inferior to that in the VAN 1 group and was superior to that of the other regimens in limiting the ocular inflammation and preserving the architecture of the ocular structures (P < 0.05). The elimination half-life (t(1/2β)) of daptomycin was independent of the administered dose (38.8 ± 16.5 h and 40.9 ± 6.7 h, respectively, for the DAP 0.2 and DAP 1 groups) and was significantly longer than the t(1/2β) of vancomycin (20.5 ± 2.0 h for the VAN 1 group) (P < 0.05). This antibiotic could therefore be considered for the treatment of intraocular infections caused by Gram-positive bacteria.